Third trimester anemia extends the length of hospital stay after delivery - Koyuncu, Kazibe (Turk J Obstet Gynecol, 2017)
OBJECTIVE: To assess the relationship between maternal third trimester anemia and hospital stay after delivery. MATERIALS AND METHODS: In this retrospective cross-sectional study, 695 women aged 18-42 years were included between January 2016 and June 2016. Obstetric outcomes and fetal outcomes were measured. Statistical analysis was performed using SPSS, version 19.0 (SPSS, Chicago, Illinois). RESULTS: The prevalence of anemia in this study was 15.2%. The study population was divided into three groups according to hemoglobin (Hb) levels. Group 1 consisted of patients with Hb <8.5 g/dL, group 2 Hb 8.5-11 g/dL, and group 3 Hb >11 g/dL. Higher levels of Hb were associated with shorter stay in hospital (p=0.028). In binary comparison, no significant difference was observed between groups 2 and 3, whereas it was statistically different from group 1. Fetal weight (p=0.562), neonatal intensive care unit admission (p=0.596), APGAR score 1(st) (p=0.674) and 5(th) minute (p=0.876), type of delivery (p=0.831), and gestational age (p=0.798) were not statistically different between the groups; however, hospitalization time was significantly different (p=0.028). CONCLUSION: Maternal anemia in the third trimester prolongs hospitalization time after delivery. Anemia effects pregnancy and the fetus in the postpartum period in addition to the prenatal period.